1989
DOI: 10.1177/070674378903400211
|View full text |Cite
|
Sign up to set email alerts
|

Biologic Markers and Bipolar Disease in Children

Abstract: The diagnosis of manic depressive or bipolar disease is difficult in adolescents. Poorly defined nosology, and a high incidence of schizophrenia-like symptoms contribute to this difficulty. The authors discuss the use of the Dexamethasone Suppression Test (DST) in the diagnosis of bipolar disease in adolescents, presenting three case studies. The existence of phase-dependent DST non-suppression is described for the first time in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…There is evidence of DST nonsuppression and elevated cortisol levels in bipolar adults with mixed states [14]. Woodside et al [78] reported on phasedependent DST non-suppression in three adolescents with bipolar disorder. DST was non-suppressed in the depressed or mixed phase.…”
Section: Neurobiologymentioning
confidence: 99%
“…There is evidence of DST nonsuppression and elevated cortisol levels in bipolar adults with mixed states [14]. Woodside et al [78] reported on phasedependent DST non-suppression in three adolescents with bipolar disorder. DST was non-suppressed in the depressed or mixed phase.…”
Section: Neurobiologymentioning
confidence: 99%